Pengaruh Stress Kerja dan Konflik dengan Rekan Kerja terhadap Kebahagiaan Karyawan Dimoderasi oleh Kepuasan Kerja - Adinda Pujakusuma; Andriyastuti Suratman (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to examine the influence of job stress and coworker conflict on employee happiness, and the role of job satisfaction as a moderating variable in these relationships. The research is grounded in the importance of addressing employees’ psychological well-being amidst workplace pressure and interpersonal dynamics. A quantitative approach was employed by distributing questionnaires to 381 employees working at a company in Yogyakarta. Descriptive statistical analysis was used to process the data. The results show that job stress does not have a significant effect on employee happiness. In contrast, coworker conflict negatively affects employee happiness. Furthermore, job satisfaction does not moderate the relationship between job stress and happiness, but it does moderate the relationship between coworker conflict and happiness. These findings suggest that job satisfaction can help buffer the negative effects of interpersonal conflict at work, although it is not sufficient to reduce the impact of job stress on happiness.